2012
DOI: 10.5424/fs/2012213-02348
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal and non-stomatal limitations on leaf carbon assimilation in beech (Fagus sylvatica L.) seedlings under natural conditions

Abstract: Limitations to diffusion and biochemical factors affecting leaf carbon uptake were analyzed in young beech seedlings (Fagus sylvtica L.) growing in natural gaps of a beech-wood at the southern limit of the species. Half of the seedlings received periodic watering in addition to natural rainfall to reduce the severity of the summer drought. Plant water status was evaluated by measuring predawn water potential. Basic biochemical parameters were inferred from chlorophyll fluorescence and photosynthesis-CO 2 curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
(107 reference statements)
2
12
0
Order By: Relevance
“…Leaf physiological responses were observed first for stomatal conductance ( g S ), intercellular CO 2 concentration ( c i ) and net-photosynthesis ( A N ), which started to decrease when ψ pd dropped below -0.6 MPa. Previous studies on beech showed similar responses of g S and A N to decreasing ψ pd , suggesting that a ψ pd of around -0.6 MPa represents a general threshold for drought effects on beech leaf gas exchange ( Aranda et al, 2012 ; Cocozza et al, 2016 ).…”
Section: Discussionmentioning
confidence: 59%
“…Leaf physiological responses were observed first for stomatal conductance ( g S ), intercellular CO 2 concentration ( c i ) and net-photosynthesis ( A N ), which started to decrease when ψ pd dropped below -0.6 MPa. Previous studies on beech showed similar responses of g S and A N to decreasing ψ pd , suggesting that a ψ pd of around -0.6 MPa represents a general threshold for drought effects on beech leaf gas exchange ( Aranda et al, 2012 ; Cocozza et al, 2016 ).…”
Section: Discussionmentioning
confidence: 59%
“…• The degree of stress tolerance might also reflect likelihood to migrate to higher elevations under climate change; a scenario sometimes predicted for beech populations (Sabaté et al 2002). Low photosynthetic rates and stomatal conductances under stressful summer conditions, of high evaporative demand and low soil moisture, have previously been reported for northern range-edge provenances compared to the other beech populations (Aranda et al 2012;Robson et al 2012;Sánchez-Gómez et al 2013). Hence, we expected the provenance from the northern range margin to have the lowest capacity to cope with drought stress during this experiment, reflected in lower photosynthetic rates in the sun and poorest control of water loss in general (Hypothesis 3).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 61%
“…; Aranda et al . ). Sessile oaks had higher (less negative) Ψ pd than beech trees, suggesting sessile oak trees were able to extract water from deeper soil layers and hence were less affected by summer shortage of rainfall (Leuschner et al .…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, the biochemistry related with carbon fixation, that is estimated through V Cmax , was unaffected by water stress, as recently shown in beech seedlings (Aranda et al . ).…”
Section: Discussionmentioning
confidence: 97%